PENGARUH BUDAYA ORGANISASI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA DIVISI HRD PT. KERTA RAJASA RAYA SIDOARJO - BAGUS AFRIZAL ARIFANI, M (Jurnal Ilmu Manajemen (JIM), 2018)
This study aims to analyze the influence of organizational culture and compensation on employee performance. The sample used in this study amounted to 32 employees ie all employees in the division of HRD PT. Kerta Rajasa Raya Sidoarjo. Data analysis technique used is multiple linear regression analysis with the help of software SPSS 16. The results of this study show that organizational culture has a positive and significant effect on employee performance. Compensation has a significant effect on employee performance. Organizational culture and compensation affect simultaneously to employee performance. Employees in the HRD division of PT. Kerta Rajasa Raya feels there is a healthy competition in the place where they work, and employees feel the company always provide incentives to employees who exceed the performance standards specified by the company, and also there is the fact that the company always provide incentives to employees every year . Keywords: Organizational Culture, Compensation, Employee Performance